The “No ARSA” Sign: A Novel Method of Prenatal Screening for Aberrant Right Subclavian Artery - Kassif, Eran (J Clin Med, 2020)
An aberrant right subclavian artery (ARSA) can be overlooked by the conventional method as described by Chaoui et al., due to acoustic shadowing. The aim of this study was to evaluate the feasibility and accuracy of a novel screening method for ARSA by demonstrating the brachiocephalic artery bifurcation, referred to as the “No ARSA” sign. A prospective study conducted at a tertiary care center between 2018 and 2019 included unselected pregnant patients at a median gestational age of 15.1 (14.2–22.1; IQR (inter-quartile range)) weeks, who had been referred for a routine or targeted anomaly scan. All participants were scanned for the presence or absence of ARSA using both the conventional and the novel “No ARSA” methods for validation purposes. A total of 226 unselected patients were enrolled in the study. The “No ARSA” sign was visualized in 218 fetuses (96.5%). In the remaining 8 cases (3.5%), the “No ARSA” sign was not demonstrated. In these fetuses, an ARSA was visualized by the conventional method. The new method exhibited 100% feasibility and was in complete agreement with the conventional method. Intra- and inter-observer agreement was excellent (κ = 1). The results of the study suggest that the “No ARSA” sign is an efficient and reliable screening tool for ARSA.